The Inverse Correlation Between the Duration of Lifetime Occupational Radiation Exposure and the Prevalence of Atrial Arrhythmia - Thirumal, Rithika; Vanchiere, Catherine; Bhandari, Ruchi; Jiwani, Sania; Horswell, Ronald; Chu, San; Chamaria, Surbhi; Katikaneni, Pavan; Boerma, Marjan; Gopinathannair, Rakesh; Olshansky, Brian; Bailey, Steven; et al. (Frontiers in Cardiovascular Medicine, 2022)
OBJECTIVE: Advancements in fluoroscopy-assisted procedures have increased radiation exposure among cardiologists. Radiation has been linked to cardiovascular complications but its effect on cardiac rhythm, specifically, is underexplored. METHODS: Demographic, social, occupational, and medical history information was collected from board-certified cardiologists via an electronic survey. Bivariate and multivariable logistic regression analyses were performed to assess the risk of atrial arrhythmias (AA). RESULTS: We received 1478 responses (8.8% response rate) from cardiologists, of whom 85.4% were male, and 66.1% were ≤65 years of age. Approximately 36% were interventional cardiologists and 16% were electrophysiologists. Cardiologists >50 years of age, with >10,000 hours of radiation exposure, had a significantly lower prevalence of AA versus those with ≤10,000 hours (11.1% vs 16.7%, p=0.019). A multivariable logistic regression was performed and among cardiologists >50 years of age, exposure to >10,000 radiation hours was significantly associated with a lower likelihood of AA, after adjusting for age, sex, diabetes mellitus, hypertension, and obstructive sleep apnea (adjusted OR 0.57; 95% CI 0.38-0.85, p=0.007). The traditional risk factors for AA (age, sex, hypertension, diabetes mellitus, and obstructive sleep apnea) correlated positively with AA in our data set. Cataracts, a well-established complication of radiation exposure, were more prevalent in those exposed to >10,000 hours of radiation versus those exposed to ≤10,000 hours of radiation, validating the dependent (AA) and independent variables (radiation exposure), respectively. CONCLUSION: AA prevalence may be inversely associated with radiation exposure in Cardiologists based on self-reported data on diagnosis and radiation hours. Large-scale prospective studies are needed to validate these findings.